Analysis of the Coupling Efficiency of a Dual-Fiber Spherical Coupler and Improvement of the Coupling Efficiency with a Polished Spherical Coupler - Yuanzheng Chen; Jiwen Cui; Jiubin Tan (IEEE Photonics Journal)
Efficient coupling of light from one waveguide to another is essential for many applications. The structural complexity of the coupler and the boundary discontinuity makes analyzing and improving the light energy coupling efficiency challenging. A dual-fiber spherical coupler, widely used in many fields, has a rather low coupling efficiency of 10%. The reasons for such low coupling efficiency have not yet been discussed, and effective methods for improving the coupling efficiency of this coupler have not been proposed. The coupling efficiency of the coupler is analyzed by using a proposed one-dimensional quantum tunneling model, and a polished spherical coupler is designed and fabricated to improve it. The main reason for the low coupling efficiency is that light has a rather high probability of refracting and then escaping at the boundary and that light reflects too many times inside the coupler. The polished coupler proposed effectively improved the coupling efficiency from 10% to 22.9%. This study will help researchers to design spherical couplers and promote their potential use.